Antimicrobial resistance in bacterial wound, skin, soft tissue and surgical site infections in Central, Eastern, Southern and Western Africa: A systematic review and meta-analysis - Monk, Edward J. M; Jones, Timothy P. W; Bongomin, Felix; Kibone, Winnie; Nsubuga, Yakobo; Ssewante, Nelson; Muleya, Innocent; Nsenga, Lauryn; Rao, V. Bhargavi; van Zandvoort, Kevin (Public Library of Science, 2024)
Abstract Antimicrobial resistance (AMR) is a major global threat and AMR-attributable mortality is particularly high in Central, Eastern, Southern and Western Africa. The burden of clinically infected wounds, skin and soft tissue infections (SSTI) and surgical site infections (SSI) in these regions is substantial. This systematic review reports the extent of AMR from sampling of these infections in Africa, to guide treatment. It also highlights gaps in microbiological diagnostic capacity. PubMed, MEDLINE and Embase were searched for studies reporting the prevalence of Staphylococcus aureus , Eschericheria coli , Klebsiella pneumoniae , Pseudomonas aeruginosa and Acinetobacter baumannii in clinically infected wounds, SSTI and SSI in Central, Eastern, Southern or Western Africa, and studies reporting AMR from such clinical isolates. Estimates for proportions were pooled in meta-analyses, to estimate the isolation prevalence of each bacterial species and the proportion of resistance observed to each antibiotic class. The search (15 th August 2022) identified 601 articles: 59 studies met our inclusion criteria. S . aureus was isolated in 29% (95% confidence interval [CI] 25% to 34%) of samples, E . coli in 14% (CI 11% to 18%), K . pneumoniae in 11% (CI 8% to 13%), P . aeruginosa in 14% (CI 11% to 18%) and A . baumannii in 8% (CI 5% to 12%). AMR was high across all five species. S . aureus was resistant to methicillin (MRSA) in >40% of isolates. E . coli and K . pneumoniae were both resistant to amoxicillin-clavulanic acid in ≥80% of isolates and resistant to aminoglycosides in 51% and 38% of isolates respectively. P . aeruginosa and A . baumannii were both resistant to anti-pseudomonal carbapenems (imipenem or meropenem) in ≥20% of isolates. This systematic review found that a large proportion of the organisms isolated from infected wounds, SSTI and SSI in Africa displayed resistance patterns of World Health Organisation (WHO) priority pathogens for critical or urgent antimicrobial development.
Keywords: Antimicrobial resistance; bacterial wound; surgical site infections; Central, Eastern, Southern and Western Africa